Potential role of vacuum-assisted procedures in resecting breast cancers and highlighting selection criteria to support future trials - Valadares, C. N.; Couto, H. L.; Soares, A. N.; Toppa, P. H.; Ricardo, B. P.; McIntosh, S. A.; Sharma, N.; Resende, V. (Frontiers in Oncology, 2023)
Purpose: The role of vacuum assisted biopsy in resecting breast cancers. Methods: Retrospective database analysis of 116 cancers (both invasive breast cancers (IC) or ductal carcinoma in situ (DCIS)) diagnosed by vacuum assisted biopsy (VAB) submitted to standard surgical treatment with complete histological data from VAB and surgery. Excision following VAB was defined as complete resection (CR) if there was no residual tumor in the surgical specimen, minimal residual disease (MRD) if residual tumor ≤3mm, gross residual disease (GRD) if residual tumor >3mm and upgrade from DCIS on VAB to IC. CR and MRD were combined as potentially resected percutaneously (PRP). GRD and those with upgrade to IC were determined not eligible for percutaneous resection (NPR). Factors predictive of PRP were evaluated. Results: Mean age was 55.6 years (20-91; SD 12,27). CR was seen in 29/116 cases (25%), MRD in 18/116 cases (15.5%), GRD in 64/116 cases (55.2%) and 5/116 cases (4.3%) were upgraded from DCIS to IC, and those groups combined represented 47 cases of PRP (40.5%) and 69 (59,5%) of NPR. For 77 tumors ≤10mm, 45 (58.5%) were PRP. Multivariate analysis reveals significance for enlarged VAB (EVAB) (p=0.008, OR: 4.4, 95% CI), low/intermediate nuclear grade (p<0.001, OR: 12.5, 95% CI) and final tumor size (T) ≤10mm (p=0.001, OR: 50.1, 95% CI) for PRP. Conclusions: This study showed that lesions completely excised with VAB that were cancer could have been treated with vacuum assisted biopsy rather than surgery but tumor selection in terms of subtype and size is important.